2011
DOI: 10.5897/ajpp11.159
|View full text |Cite
|
Sign up to set email alerts
|

Effects of endurance training on exhaustive exercise-induced oxidative stress markers

Abstract: This study was aimed to investigate the effects of endurance training on lipid peroxidation and antioxidant enzyme levels in young adults. Twenty four male students participated in this study. Subjects were divided into two groups as training group (n=12) and control group (n=12). Subjects in the training groups performed running exercise 25 to 60 min/day, three days/week for eight weeks at an intensity of 50 to 70% of target heart rate. Blood samples collected at rest and after exhaustive exercise before and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 24 publications
0
6
0
1
Order By: Relevance
“…To estimate aerobic power by maximal oxygen consumption values (VO 2max ), the Bruce treadmill protocol was used [ 30 ]. Briefly, participants ran on a treadmill completing an exhaustive running test.…”
Section: Methodsmentioning
confidence: 99%
“…To estimate aerobic power by maximal oxygen consumption values (VO 2max ), the Bruce treadmill protocol was used [ 30 ]. Briefly, participants ran on a treadmill completing an exhaustive running test.…”
Section: Methodsmentioning
confidence: 99%
“…The beneficial effects of aerobic exercise training on antioxidant defense mechanisms in several tissues have been reported [12] [18]. Revan and Erol [19] have observed in subjects who performed a protocol of physical training in the intensity of 50% to 70% of maximum heart rate. It was able to reduce the levels of lipid peroxidation in erythrocytes after exhaustive exercise.…”
Section: Introductionmentioning
confidence: 94%
“…The group of rats given a combination dose of GME and VPE with a ratio of 75:25 and 50:50 showed the same and significantly different reduction in MDA when compared to a dose of 25:75. Increased levels of MDA in the control group due to the production of free radicals caused by physical activity exceeds the body's antioxidant cellular defense resulting in oxidative stress (Jackson et al, 2016;Revan and Erol, 2011). As is known Malondialdehyde (MDA) is one of the results of lipid peroxidation caused by free radicals during maximum physical exercise or endurance training with high intensity (Tsikas, 2017).…”
Section: Levels Of Mda and Gpxmentioning
confidence: 99%
“…Oxidative stress conditions also affect the hematological profile (Abdel-Moneim et al, 2019a), which is thought to be due to the release of inflammatory mediators (Boskabady and Farhadi, 2008). Aerobic exercise can increase oxygen consumption 10-20 times in the body and 100-200 times in skeletal muscle (Revan and Erol, 2011). Several recent investigations have found that NADPH oxidase enzymes in the skeletal play a signaling role in physiological responses to exercise and that they, together with xanthine oxidase enzymes, may contribute to the relative increase in whole-body oxidation (Jackson et al, 2016).…”
Section: Introductionmentioning
confidence: 99%